Web-Based Triage Analysis (Triage Go) on Speed and Accuracy of Service - Ramliana, Adhy; Triyanto, Endang (Indonesian Journal of Global Health Research, 2025)
The increasing number of visits to the ER requires nurses and ER staff to move quickly in assessing the condition and sorting patients based on their severity. This is to determine the priority of patient management. The administrative process for registration often takes a long time so that nurses still use paper to perform initial triage on patients. In this digital era, technology-based solutions are becoming increasingly relevant, especially with the increasing use of digital platforms worldwide. Method: Article search using electronic databases such as Pubmed, Science direct, and Google Scholar. The search for articles used were articles published in 2019-2024, using the keywords "Triage" AND "Web Triage" AND "Speed" OR "Accuracy" OR "ER Service". Results: Based on 10 articles obtained, it was found that the use of Web-based Triage is one of the implementations of innovation that can be applied to improve the quality of service time in the ER. Analysis of web-based Triage (TRIAGE GO) can influence the speed and accuracy of service in the ER of Cilacap Regional Hospital. Conclusion: Web-based triage system as the best solution to optimize services in Emergency Installation.